2017
DOI: 10.5539/ibr.v10n6p75
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Corruption on Entrepreneurial Intention: Evidence from Italy

Abstract: This paper aims to examine the entrepreneurial intention of undergraduate students, using a modified version of Ajzen's theory of planned behavior (TPB), considering the perception of corruption. We conducted a questionnaire survey with Italian students. There were a total of 350 student participants. In order to analyze the data collected with the questionnaire, structural equation modeling is provided. Our results indicate that the majority of students have strong entrepreneurial intention but due to the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Such results seem to confirm-indirectly and at an individual level of analysis-the hypothesis formulated by Harbi and Anderson (2010) regarding the role of corruption as a grease-the-wheel factor affecting entrepreneurial intentions. The only exception contrasting this hypothesis is represented by the work of Allini et al (2017), which displays a negative relationship between corruption and entrepreneurial intentions.…”
Section: The Effects Of Corruption On Entrepreneurial Intentions: Thementioning
confidence: 90%
See 1 more Smart Citation
“…Such results seem to confirm-indirectly and at an individual level of analysis-the hypothesis formulated by Harbi and Anderson (2010) regarding the role of corruption as a grease-the-wheel factor affecting entrepreneurial intentions. The only exception contrasting this hypothesis is represented by the work of Allini et al (2017), which displays a negative relationship between corruption and entrepreneurial intentions.…”
Section: The Effects Of Corruption On Entrepreneurial Intentions: Thementioning
confidence: 90%
“…Studies focused on the effects of the corruption of an entrepreneurial ecosystem on entrepreneurial intentions have reported conflicting results. Allini et al (2017) underlined that Italian college business students' entrepreneurial intentions are negatively predicted by the perception of the pervasiveness of corruption in the entrepreneurial ecosystem, since it produces a climate of distrust (Ciziceno and Travaglino 2019) and a perceived reduction in the probability of business success. This study seems to confirm the sand-the-wheel hypothesis.…”
Section: The Effects Of Corruption On Entrepreneurial Intentions: Thementioning
confidence: 99%
“…Although the majority of studies seem to confirm the "sand the wheel" hypothesis as the one that better explains the relationship between entrepreneurship, economic growth, and corruption (Aidt 2009;Allini et al 2017;Bowen and De Clercq 2008;Del Mar Salinas-Jiménez and Salinas-Jiménez 2007;Djankov et al 2005;Dutta and Sobel 2016;Estrin et al 2006; Olawale and Garwe 2010), El Harbi and Anderson (2010) have developed an econometric model that indirectly supports the "grease the wheel" hypothesis (Hofstede et al 2004), as they showed that lower levels of perceived corruption were associated with lower levels of self-employment. These authors suggest that this apparently counter-intuitive and counter-trend result could be explained by taking into account entrepreneurs' resignation to, and understanding of, corruption as something they are used to and against which they have developed specific competencies (El Harbi and Anderson 2010).…”
Section: The Effect Of Corruption Perception Of the Entrepreneurship mentioning
confidence: 99%
“…With regard to the first way, Allini et al (2017) tried to incorporate in the TPB model the perceived corruption as a contextual factor that can inhibit the development of EI in young aspiring entrepreneurs demonstrating that perceived corruption might have a detrimental effect on EI creating a culture of mistrust. Keat et al (2012) openly reasoned about two categories of perceived obstacles that could negatively affect the intention of an aspiring entrepreneurs in starting a new firm: endogenous obstacles, linked to the beliefs showed by the individuals about their attitude and other personal characteristics; exogenous obstacles, linked to the individual perception about factors that can be seen as difficulties generated by the policies adopted by government (e.g, bureaucracy, lack of funds, etc.).…”
Section: Problem Statementmentioning
confidence: 99%